The Influence of Leadership Communication Relationship on Work Spirit of Housekeeping Employees at Hotel Angkasa Raya, Sidikalang City, Dairi Regency - Booni Tauhid (Politeknik Pariwisata Medan, 2021)
Communication between leadership groups is very important if within the scope of work, good communication between leaders and housekeeping employees will have a positive impact on the morale of housekeeping employees, in this study. The purpose of this study is to determine the communication between leadership and housekeeping and to find out the extent of communication that has been established for the advancement of the hotel which is the object of this study. Data collection methods or techniques using population and samples, data collection techniques namely questionnaires, observation, documentation, and literature study. Sources of data used are primary data sources and secondary data sources. The data were obtained through distributing questionnaires to respondents, then the respondents' answers were processed using SPSS 16 with correlation analysis. The purpose of this study was to determine the relationship between leadership and housekeeping employees on morale at Angkasa Raya Hotel Sidikalang